Early career professionals: A challenging road. Issue 1 (5th January 2018) - Kulkarni, Ketan; Muia, Joshua; Boulaftali, Yacine; Blondon, Marc; Lauw, Mandy N.
Abstract: The term "early career professional" (ECP) indicates a generation of professionals that demonstrates the potential to succeed established professionals and leaders. The field of thrombosis and hemostasis has a large ECP community. They often face typical challenges in their endeavor to establish an independent academic career. A healthy work‐life balance and mentoring are key for ECPs to create the ideal circumstances to advance their careers. However, multitasking training, research and clinical duties is a burden, and burnout is a looming issue. The advent of the smartphone presents an additional challenge by blurring the border between work and non‐work time. This Forum describes some of the typical challenges faced by ECPs, highlights existing literature and suggests practical solutions relevant to ECPs in the field of thrombosis and hemostasis, and the possible role of the ISTH Early Career Committee.